High carbohydrate diet induced endoplasmic reticulum stress and oxidative stress, promoted inflammation and apoptosis, impaired intestinal barrier of juvenile largemouth bass (Micropterus salmoides). Issue 119 (December 2021) - Zhao, Liulan; Liang, Ji; Chen, Fukai; Tang, Xiaohong; Liao, Lei; Liu, Qiao; Luo, Jie; Du, Zongjun; Li, Zhiqiong; Luo, Wei; Yang, Song; Rahimnejad, Samad
Abstract: This study assessed the effects of feed carbohydrate content on intestinal physical barrier and immunity in juvenile largemouth bass ( Micropterus salmoides ). Triplicate groups of juvenile fish (4.1 ± 0.2 g) were fed low (LCD, 7%), medium (MCD, 12%) and high (HCD, 17%) carbohydrate diets for eight weeks. Gut histology revealed the slight infiltration of inflammatory cells and moderate loss of mucous membrane layer in HCD group. Expression of ZO1, occluding, and claudin7 genes and epidermal growth factor receptor ( EGFR ) gene were significantly decreased in HCD group indicating the impairment of tight junction and epithelial cell regeneration. The results showed the significant ( P < 0.05) reduction of antioxidant capacity in HCD group compared to LCD. Furthermore, expression of intestinal ERS-related genes such as IRE1, Eif2α, GRP78, CHOPα and CHOPβ in HCD group was significantly higher than the LCD group. In addition, HCD induced the up-regulated expression of inflammatory ( IL-8, IL-1β, TNFα and COX2 ) and apoptosis ( TRAF2, bax, casepase3, caspase8 and casepase9 ) related genes in fish intestine. The data generated in this study clearly demonstrated that HCD induced ERS and oxidative stress, which promoted intestinal inflammation and apoptosis in juvenile largemouth bass. Highlights: High carbohydrate diet (HCD) induced intestinal endoplasmic reticulum stress, apoptosis and inflammation. HCD inhibited epithelial cell renewal and impaired tight junction resulting in the impairment of intestinal barrier. Intestinal barrier deterioration was aggravated by oxidative stress, choric ERS, excessive inflammation and apoptosis.